Reviving the Narrative of Muhammad's Life: Tariq Ramadan's Interpretative Strategies and Ethical Contextualization - Mukhlisin Saad (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
This article delves into the intellectual landscape of Tariq Ramadan, focusing on his approach to interpretation and contextualization. The analysis centers on Ramadan’s work, In the Footsteps of the Prophet: Lessons from the Life of Muhammad, which, despite its biographical nature, unveils a profound connection between his thoughts and the art of interpretation and contextualization. The article contends that while Ramadan may not align himself explicitly with the tradition of reinterpretation or contextualization, his practical methodologies reflect interpretive strategies that breathe new life into historical texts, adapting them to contemporary contexts. Moreover, this paper argues that Ramadan’s contextual interpretations are deeply rooted in ethics, underpinned by the belief in their universal applicability across diverse conditions. These ethical values, as delineated by Ramadan, serve as a bridge between the past and the present, as they are seamlessly interwoven with educational narratives drawn from the life of Prophet Muhammad. These narratives not only provide a basis for Muslims to rekindle the prophetic ideals in the modern era but also offer a compelling framework for fostering moral and ethical guidance in a rapidly changing world. In this intricate web of interpretation and contextualization, Tariq Ramadan’s work emerges as a significant contribution to the ongoing discourse on Islamic thought and its relevance in contemporary society.